Comparison of outcomes of conventional septoplasty vs conservative endoscopic septoplasty - Liaqat, Arslan; Abro, Laraib; Latif, Sarfraz; Anwaar, Anam; Arshad, Gulnaz; Yaqub, Aqsa (International Journal of Pathology, 2026)
background and objective: Nasal obstruction is a prevalent issue in rhinologic practice, with a deviated nasal septum being a primary cause. The assessment of septal deviation, which contributes to nasal obstruction, largely relies on physical examinations and imaging techniques. This study was conducted to compare the outcome of conventional septoplasty and conservative endoscopic septoplasty for symptomatic deviated nasal septum. Methodology: The ENT department of Sheikh Zayed Hospital, Lahore carried out this randomized controlled study (Clinictrials.gov Identifier: NCT07434765). Total 210 adults between ages of 16 and 50 years who have been diagnosed with DNS were included. individuals with allergic rhinitis, vasomotor rhinitis, acute infections and other systemic illness and undergone other nasal procedures such as turbinectomy were excluded. A sample of 210 cases were randomized into two groups based on the lottery method; 105 were undergone conventional septoplasty (group A) and 105 were undergone conservative endoscopic septoplasty (group B). Post-operative follow up was done to evaluate symptom relief (nasal obstruction, headache, nasal discharge), endoscopic findings (residual deviation, septal perforation, synechiae formation, delayed healing), and operative outcome (intra-operative blood loss and operative duration). Results: In this study, group A’s mean operative time and intra-operative blood loss were 44.87 +- 11.14 minutes and 72.90 +- 10.78 ml respectively while group B’s was 32.20 +- 7.89 minutes and 51.07 +- 6.77 ml. Post-operative nasal obstruction, headache and nasal discharge at three weeks were 6.67%, 9.25% and 5.71% in group A and 0.95%, 1.90% and 0.95% in group B. Conventional septoplasty had a substantial higher residual deviation, septal perforation and synechiae formation than endoscopic septoplasty (7.62% vs 1.90%, 6.67% vs 0.95% and 11.43% abd 2.86%). Conclusion: in contrast to traditional septoplasty, endoscopic septoplasty showed better post-opertative symptom alleviation and fewer complications in this study.